Komponen Informasi dan Komunikasi Serta Pemantauan Atas Siklus Pengeluaran - Hera Khairunnisa (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
This research aims to analyze and give suggestion on internal control system in expenditure cycle of Unit A by comparing components on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) internal control framework that consisted of environment control, risk assess-ment, control activity, information and communication, and monitoring. The method of analysis data is using qualitative analysis by gathering data with interview, document review, and literature review. Conclusion from information and communication component is that the entity does not have standard information on the completeness of supporting data for cash disbursement transactions. Conclusion of monitoring is that the logistic manager has not conducted optimal monitoring of the process of receiv-ing goods in the warehouse.